The Power of Information: Impact of Knowledge Sharing Agri Portals in Rural India - Yadav, Kiran; Sharma, Gyanendra (Journal of Agricultural Extension Management, 2019)
In agriculture and rural development, a variety of fairly large-scale andmature ICT-enabled projects are providing social and economic value allalong the agro-value chain by filling the information gap for the farmers. Suchprojects, directly linked to income-generating activities, have visible directeconomic value for end-users. The large projects have impact on up to severalmillion rural dwellers, while benefiting all actors of rural development.However, the impact assessment of these projects is still an open issue in termsof methodology and results, which leads to failure of many such ICT initiativesespecially in agriculture. The present study is an effort towards assessing twosuch ICT initiatives in agriculture launched by the Government of India.